Current research on surface finishing and coatings for aerospace bodies and structures - a review. (1st May 2013) - Larson, C; Smith, J R; Armstrong, G J
<x xml:space="preserve">Abstract</x> This review reports recent developments of new coatings and surface treatments for aerospace bodies and structures. Advances in the field have been driven by the need for materials with improved performance characteristics and also by environmental legislative pressures. The traditional areas of corrosion and wear resistance are still receiving the greatest focus, although interest in other properties and the increasing use of composites continue to emerge.